An Efficient Process for Recycling Nd–Fe–B Sludge as High-Performance Sintered Magnets. (February 2020) - Yin, Xiaowen; Yue, Ming; Lu, Qingmei; Liu, Min; Wang, Feng; Qiu, Yubing; Liu, Weiqiang; Zuo, Tieyong; Zha, Shanshun; Li, Xuliang; Yi, Xiaofei
Abstract: Given the increasing concern regarding the global decline in rare earth reserves and the environmental burden from current wet-process recycling techniques, it is urgent to develop an efficient recycling technique for leftover sludge from the manufacturing process of neodymium–iron–boron (Nd–Fe–B) sintered magnets. In the present study, centerless grinding sludge from the Nd–Fe–B sintered magnet machining process was selected as the starting material. The sludge was subjected to a reduction–diffusion (RD) process in order to synthesize recycled neodymium magnet (Nd2 Fe14 B) powder; during this process, most of the valuable elements, including neodymium (Nd), praseodymium (Pr), gadolinium (Gd), dysprosium (Dy), holmium (Ho), and cobalt (Co), were recovered simultaneously. Calcium chloride (CaCl2 ) powder with a lower melting point was introduced into the RD process to reduce recycling cost and improve recycling efficiency. The mechanism of the reactions was investigated systematically by adjusting the reaction temperature and calcium/sludge weight ratio. It was found that single-phase Nd2 Fe14 B particles with good crystallinity were obtained when the calcium weight ratio (calcium/sludge) and reaction temperature were 40 wt% and 1050 °C, respectively. The recovered Nd2 Fe14 B particles were blended with 37.7 wt% Nd4 Fe14 B powder to fabricate Nd–Fe–B sintered magnets with a remanence of 12.1 kG (1 G = 1 × 10 −4 T), and a coercivity of 14.6 kOe (1 Oe = 79.6 A·m −1 ), resulting in an energy product of 34.5 MGOe. This recycling route promises a great advantage in recycling efficiency as well as in cost.